Green Financial Instrument: The Role of Productive Zakat in Achieving Sustainable Development Goals (SDGS) - Dedi Suselo; Achmad Luthfi Chamidi; Ahmad Zainal Abidin; Rohkmat Subagiyo; Binti Nur Asiyah (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2026)
Sustainable Development Goals (SDGs) are a global transformation agenda initiated by the United Nations in 2015. Indonesia, as one of the member states, faces multidimensional challenges in implementing SDGs. One of the promising strategies in Islamic social finance is the productive zakat program managed by BAZNAS, which aligns with poverty alleviation, education access, and inclusive economic growth. This research aims to analyze the implementation of productive zakat as a green financial instrument to accelerate the achievement of SDGs in Indonesia. The study offers a conceptual and empirical model integrating Islamic financial principles and national development planning to optimize zakat for sustainable transformation. It fills the gap by linking productive zakat with thematic SDGs targets in a structured governance model. The research applies a qualitative-descriptive approach using secondary data sources from BAZNAS reports, national zakat databases, and academic studies. Content analysis is used to examine the contribution of zakat programs toward SDGs indicators. Zakat significantly contributes to SDG 1 (No Poverty), SDG 3 (Good Health), SDG 4 (Quality Education), and SDG 8 (Economic Growth), with effective programs like Z-Mart, BAZNAS Health Clinics, and scholarship schemes. Challenges include low public literacy and the need for digitalized zakat tracking systems. The study proposes a strategic model—“Zakat for Sustainable Indonesia”—emphasizing spatial-thematic mapping, multi-stakeholder integration, and digital monitoring systems to improve zakat’s effectiveness in SDGs achievement.